The prenatal ultrasonic character and postnatal follow-up of 227 microcystic and macrocystic congenital cystic adenomatoid malformations. (19th May 2021) - Chen, Yuan; Zhao, Baihui; Xi, Fangfang; Wang, Yayun; Yang, Mengmeng; Luo, Qiong
Abstract: The objective of our study was to compare microcystic and macrocystic congenital cystic adenomatoid malformation (CCAMs) through prenatal characteristics, perinatal outcome, postnatal management and development after consultation in our prenatal diagnosis centre. We conducted a retrospective cohort study of 227 cases prenatally diagnosed as CCAM in our hospital within three years. One hundred and eighty-one cases continued their pregnancy and 46 pregnancies were terminated. One hundred and fifteen of 227 cases were microcystic and 112 were macrocystic. The prenatal ultrasound characteristics of two types showed no statistically significant differences, despite that CVR of macrocystic CCAMs was mildly greater than microcystic. None of recorded cases received surgical intervention in utero . Compared with healthy foetuses, CCAMs presented with higher percentage of polyhydramnios and male foetuses, larger amount of postpartum blood loss and longer duration of NICU hospitalisation. Compared with 46 legal abortions, continued pregnancy cases had a smaller CVR, less polyhydramnios, cardiac shift and hydrops. One hundred and seventy-nine cases were followed up after birth and 174 babies were asymptomatic. Thirty one cases received successful surgical resection. In conclusion, the prenatally diagnosed CCAMs have a good short-term prognosis and conservative management is a reasonable option in asymptomatic fetuses. Microcystic and macrocystic CCAMs both presented similar prenatal courses and perinatal prognoses. Conservative management, prenatally and postnatally, could be accepted in selected cases. Impact statement: What is already known on this subject? Congenital cystic adenomatoid malformation is a well-known developmental abnormality of the lung. The prognosis for most CCAMs is good, but the prenatal and postnatal management remains controversial. What do the results of this study add? This study is one of the largest case cohorts to conclude that microcystic and macrocystic CCAMs both presented similar prenatal courses and perinatal prognoses. Conservative management is a reasonable option in asymptomatic babies. What are the implications of these findings for clinical practice and/or further research? A comprehensive assessment by an experienced multidisciplinary team is necessary to forbid blinding abortions of CCAMs. Conservative management prenatally and postnatally could be accepted in most asymptomatic cases.